Investigating high school students’ understanding of chemical equilibrium concepts - Karpudewan, M.; Treagust, David; Mocerino, Mauro; Won, Mihye; Chandrasegaran, Chandra (2015)
© 2015 by iSER, International Society of Educational Research. This study investigated the year 12 students’ (N = 56) understanding of chemical equilibrium concepts after instruction using two conceptual tests, the Chemical Equilibrium Conceptual Test 1(CECT-1) consisting of nine two-tier multiple-choice items and the Chemical Equilibrium Conceptual Test 2(CECT-2) consisting of four structured questions. Both these tests were administered before and after the intervention. Students’ responses to the items in both the instruments indicated limited understanding of the various concepts related to chemical equilibrium. Less than 50% of the students provided correct responses to four of the nine items in the CECT-1. The total scores in the CECT-1 ranged from 0 to 8 with a mean score of 4.14 (out of a maximum of 9). In the CECT-2 the total scores ranged from 7 to 17 with a mean score of 11.0 out of a maximum score of 22. Almost half the number of students (44.6%) scored less than 50% of the total marks in the CECT-2; only 0% to 42.9% of students scored the maximum possible marks for each of the four items while achievement in all four items of the CECT-2 was below 50%. The findings will be valuable and assist teachers in planning their instruction on chemical equilibrium by taking into consideration students’ preconceptions about the topic.